2021
DOI: 10.22271/phyto.2021.v10.i1ac.13659
|View full text |Cite
|
Sign up to set email alerts
|

Effect of foliar application zinc and boron on vegetative growth characters of okra

Abstract: To know the effect of zinc and boron on crop growth a field experiment was conducted at vegetable research farm, College of Horticulture and Forestry, Pasighat during the rainy season of the year 2019. Two micronutrients (Zinc and Boron) in the form of zinc sulphate and borax were taken in different concentrations (0.5, 1.0 and 1.5%) and applied at 30 and 60 DAS respectively. The results indicated that among different treatments the highest plant height (141.18 cm) at final harvest, Number of nodes per plant (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 2 publications
1
5
0
Order By: Relevance
“…In this experiment, the Si individually and the combination with other micronutrients in a saline environment was found to significantly be effective in the weight of 500-seed over control. The result is in accordance with previous findings of 1000-seed weight in okra (Kumar et al, 2021) where it is concluded that 1000-seed weight linearly increased with the foliar application of B and Zn individually and their combinations. The increase in seed weight in this work could be the result of foliar application of micronutrients on okra under a slightly saline environment.…”
Section: Discussionsupporting
confidence: 92%
“…In this experiment, the Si individually and the combination with other micronutrients in a saline environment was found to significantly be effective in the weight of 500-seed over control. The result is in accordance with previous findings of 1000-seed weight in okra (Kumar et al, 2021) where it is concluded that 1000-seed weight linearly increased with the foliar application of B and Zn individually and their combinations. The increase in seed weight in this work could be the result of foliar application of micronutrients on okra under a slightly saline environment.…”
Section: Discussionsupporting
confidence: 92%
“…Foliar application of zinc resulted in a maximum number of fruits per plant (113.99), fruit length (9.45 cm), fruit weight per plant (660.19 g), yield tons ha -1 (2.85 tons/ha), and 1000 seed weight (3.54 g) were recorded in the plot to which received zinc of 3 kg per hectares [46]. Kumar et al, [28] reported that spraying the crop with a solution containing 0.75 percent zinc and 0.25 percent boron twice, 45 and 65 days after transplanting, resulted in the highest possible green and dry yields. Spraying with zinc at a concentration of 0.75 percent was shown to be helpful in increasing both the growth and yield of the plants.…”
Section: Chilimentioning
confidence: 99%
“…Results are in agreement with the findings of Babu and Yadav (2005) who reported that application of zinc with boron increased the total sugars percentage in Khasi mandarin. Kumari and Deb (2018) reported that reducing sugar content of pineapple cv. Mauritius was significantly influenced by foliar application of ZnSO 4 at 0.5% and borax at 0.5%.…”
Section: Fruit Quality Parametersmentioning
confidence: 99%